Water use by Desertic Vegetation and its Hydrological Implications - Lahiri, A N (Annals of Arid Zone, 2016)
Water use behaviour of certain rainfed vegetation of Western Rajasthan has been quantified. Most desert trees display large water turn-over which is possibly due to their capacity to tap water from great depths. Changes in moisture conditions in the upper soil layers hardly influence the transpiration and relative turgidity of established trees. as it is discernable in their seedlings with limited root system. The consumptive use of moisture of shallow rooted plants like Pennisetum typhoides, Cyamopsis tetragonoloba, Phaseolus aconiti folius and P. aureus and of grasses with other associated vegetation have been described with special reference to rainfall and soil water conditions. Modulations in water use by vegetation suggested limited prospect of ground water recharge from sandy plains.